POSSIBILITIES OF ADVOCACY AND LOBBYING BY NON-GOVERNMENTAL ORGANIZATIONS OF THE INTERESTS OF BUSINESS ENTITIES IN UKRAINE - Vakhovych, Iryna; Smolych, Dariia (Socio-economic relations in the digital society, 2024)
The article explores the possibilities of advocacy and lobbying of the interests of business entities by non-governmental organizations, in particular public organizations, public unions whose activities are aimed at supporting the development of entrepreneurship, employers' organizations and their associations, chambers of commerce and industry. The functions of non-governmental business support organizations were considered: protection and representation of business interests in relations with authorities in order to improve the conditions for conducting business, legislation, and the elimination of regulatory barriers; legal support; informational support and training; establishment of relationships and communication support; resource support. The advocacy function of non-governmental organizations and the tools for its implementation, including participation in public councils at executive bodies, public examination of regulatory acts, and others, are analyzed in detail. The concepts of "advocacy" and "lobbying" have been thoroughly researched and delineated, in accordance with the legal definition, the subjects of implementation, and the difference in the purpose and content of the activity. The main methods of implementation of advocacy and lobbying of the interests of business entities by non-governmental organizations were analyzed, a problematic aspect was established, which consists in the fact that the methods of implementation of such activities have a lot in common, which in the future, with the introduction of the law from 2025, will lead to controversial issues in the process of detection by controlling bodies of manifestations of lobbying by non-governmental organizations, as well as the process of identification of commercial interest in the activities of non-commercial organizations when establishing the fact of lobbying is assumed to be debatable. An analysis of the legal regulation of the implementation of advocacy and lobbying in Ukraine, including by non-governmental organizations in accordance with the regulatory and legal framework of Ukraine, was carried out. The absence of the concept of "advocacy" and related concepts in the Law of Ukraine "On Lobbying" was established, which is positive, and it was clarified that the law does not apply to the activities of non-profit organizations and institutions, in particular public associations, except in cases when such activities relate to commercial interests. The possibility of implementing lobbying by non-governmental organizations was considered, provided they received the appropriate status.
Keywords: advocacy; lobbying; non-governmental organizations; entrepreneurship